The pass-through from depreciation inflation: A panel study - Ilan Goldfajn; Sergio R.C. Werlang (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2000)
The paper studies the relationship between exchange rate depreciations and inflation using a sample of 71 countries in the period 1980-1998. The main determinants of the extent of inflationary pass-through of the depreciations (appreciations) are the cyclical component of output, the extent of initial overvaluation of the real exchange rate (RER), the initial rate of inflation, and the degree of openness of the economy. The paper finds that the pass-through coefficients increase the larger is the horizon measured, with its peak at 12-months. It also finds that RER misalignment is the most important determinant of inflation for emerging markets while the initial inflation is the most important variable for developed countries. Using the estimated model, the paper predicts somewhat higher inflation than actually observed in several well known large depreciation cases, even if one takes into account existing measures of exchange rate expectations. This suggests that policy makers should use caution when using past models to predict future inflation in the aftermath of large depreciations.
Keywords: 330